Perception of Language Awareness through Framegram: A Classroom Example - Nik Azim, Nik Ahmad Farhan; Ramamurthy, Lena; Shafien, Syakirah; Mohd Nawi, Syamimie; Omar, Suhaida; Hussein, Nur Hafezah
This project outlines the context Language Awareness (LA) in one of formative assessment This project outlines the context Language Awareness (LA) in one of formative assessment structure of Advanced Grammar for Undergraduates (UBI10302): Framegram. LA is seen as a bridge to connect functional and purposeful language a given phenomena; characterised by student’s deep interest and critical thinking. While students interact as active participatory editors and publishers of their content on Instagram, such dynamic interaction emerged from the relationship between student-language-phenomena may result in a predictable output of language learning